Microstructural and Mechanical Characterization of the Laser Beam Welded SAF 2507 Super-Duplex Stainless Steel - Beáta Šimeková; Mária Dománková; Ingrid Kovaříková; Pavel Kovačócy; Maroš Martinkovič; Michal Šimek; Luke Ciuła (Metals)
The influence of laser beam welding parameters (power, welding rate, focusing, head oscillation, shielding gas) on the microstructure, mechanical properties and corrosion resistance of the super-duplex stainless steel SAF 2507 was studied in this paper. The presented results clearly report the effects of welding parameter changes on the character of the steel’s microstructure. The presence of secondary phase M2N in weld metals has an important influence on their mechanical properties. Optimal mechanical properties, an acceptable ferrite/austenite ratio, and the minimum content of M2N nitride required in the weld metal were acquired in the case the following application: 1100 W power, welding speed of 10 mm/s, focusing of 4 mm, and pure nitrogen shielding gas (20 L/min).